DETERMINANT FACTOR OF INTERNAL DIVIDEND PAYOUT RATIOS ON STATE OWNED ENTERPRISE - Priyantara, Eko; Thamrin, Hakiman (Dinasti Publisher, 2020)
These research aim to examine those impact from Growth, Firm Size, Return on Assets and Debt to Equity Ratio towards dividend policy of State-Owned Enterprises during period 2016-2018 with 46 BUMN as the research sample. In this research, the independent variables were Growth, Firm Size, Return on Assets and Debt to Equity Ratio, while the dependent variable was Dividend Payout Ratio. The results from these research found that Growth, Firm Size, Return on Assets and Debt to Equity Ratio simultaneously influence Dividend Payout Ratio of 87.71%. Return on Assets and Debt to Equity Ratio had significant negative impact on Dividend Payout Ratio, while Growth and Firm Size did not have an impact on Dividend Payout Ratio.